Peramalan Indikator Mikro Kinerja Komoditas Strategis Perkebunan Dengan Metode ARIMAX (Autoregressive Moving Average Exogenous Variabel) - Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.03.TAHUN 2019, 2019)
This paper aims to forecast various micro indicators of the performance of plantation strategic commodities, namely coffee, cocoa, pepper and sugar cane in Indonesia during the period 2019-2045. The methodology used in this paper is ARIMAX (exogenous autoregressive variable moving average). The results showed that pepper production tended to decrease. The same thing happened in the prediction of the area of ??pepper land which tended to continue to decline, while pepper productivity was relatively stable. Meanwhile, the projection of coffee commodity production, coffee area and productivity levels continue to rise. The projection of sugarcane production tends to increase despite fluctuations. Similar to the pattern of production, the area of ??sugarcane and productivity also increased. The projection of Indonesian cocoa production fluctuates and tends to increase during 2019-2045. The same conditions occur in the area of ??cocoa that continues to increase. Finally, the level of cocoa productivity is rising even though it tends to be volatile.